A longitudinal study of distress (depression and anxiety) up to 18 months after radiotherapy for head and neck cancer. Issue 8 (13th December 2012) - Neilson, Kate; Pollard, Annabel; Boonzaier, Ann; Corry, June; Castle, David; Smith, David; Trauer, Tom; Couper, Jeremy
Abstract Objective The aim of the study was to assess symptoms of depression and anxiety in patients with head and neck cancer up to 18 months after radiotherapy. Methods Prospective observational study of consecutive head and neck outpatients was conducted at a tertiary cancer centre (n = 101). Eligibility included diagnosis of cancer in the head and neck region, where the patient agreed to radiotherapy with curative intent. Data were collected before commencement of radiotherapy and 3 weeks and 18 months after completion. Symptoms of depression and anxiety were assessed by the Hospital Anxiety and Depression Scale. Tumour/treatment‐related physical symptoms were assessed using the 'Additional Concerns' subscale of the Functional Assessment of Chronic Illness Therapy for Head and Neck Cancer. Results The prevalence of identified probable cases of depression was 15% at baseline, increasing to 29% 3 weeks post‐treatment, falling to 8% at 18‐month follow‐up. The number of probable cases of anxiety was 20% at baseline, 17% at 3 weeks post‐treatment and 22% at 18‐month follow‐up. Depression scores significantly increased from baseline to 3 weeks post‐treatment and decreased at 18‐month follow‐up. Variability in depression scores was accounted for by tumour/treatment‐related physical symptoms. Anxiety scores significantly decreased between baseline and 3‐week post‐treatment and increased at 18‐month follow‐up. Younger age and more tumour/treatment‐related physical symptoms predicted anxiety scores. Conclusions The rates of depression in head and neck cancer patients increase following cancer treatment and are related to tumour/treatment‐related physical symptoms. Anxiety levels are higher pre‐treatment, lower immediately following cancer treatment but rise to near pre‐treatment levels more than a year after completion of cancer treatment. Copyright © 2012 John Wiley & Sons, Ltd.